Answer:
Step-by-step explanation: 56776
7 days I think sorry if I’m wrong
(2 − 3i) + (x + yi) = 6
We add the left hand side
(2+x) + (-3+y)i = 6
6 can be written in a+ib
6 can be written as 6 + 0i
(2+x) + (-3+y)i = 6 +0i
Now we frame 2 equations
2 + x= 6
-3 + y =0
Solve the first equation
2 + x = 6
Subtract 2 from both sides
x = 4
solve the second equation
-3 + y =0
Add 3 on both sides
y= 3
So x+yi is 4+3i
Answer:
x = -8
y = 9
Step-by-step explanation:
to solve this expression using simultaneous equation, we would say let
y =9............................................. equation 1
6x + 5y =-3............................................equation 2
substitute equation 1 into equation 2
-3 = 6x + 5y............................................equation 2
6x + 5(9) = -3
6x + 45 = -3
collect the like terms
6x = -3-45
6x = -48
divide both sides by the coefficient of x which is 6
6x/6 = -48/6
x = -8
therefore y = 9
x = -8
Answer:
0
Step-by-step explanation:
<h2><em>2</em><em>x</em><em>-</em><em>6</em><em>+</em><em>1</em><em>5</em><em>x</em><em>+</em><em>5</em><em>-</em><em>1</em><em>6</em><em>x</em><em>=</em><em>x</em></h2>
<h2><em>2</em><em>x</em><em>+</em><em>1</em><em>5</em><em>x</em><em>-</em><em>1</em><em>6</em><em>x</em><em>-</em><em>x</em><em>=</em><em>6</em><em>-</em><em>5</em></h2><h2 /><h2 /><h2><em>0</em><em>×</em><em>x</em><em>=</em><em>1</em></h2><h2 /><h2 /><h2 /><h2><em>x</em><em>=</em><em>1</em><em>÷</em><em>0</em></h2><h2 /><h2 /><h2><em>x</em><em>=</em><em>0</em></h2>